2012
DOI: 10.1007/s00104-011-2206-5
|View full text |Cite
|
Sign up to set email alerts
|

Lokale Diagnostik beim Rektumkarzinom

Abstract: Accurate pretherapeutic staging of rectal cancer is crucial for further therapeutic management and important for prognosis. The most accurate diagnostic tools in the assessment of T and N categories of rectal cancer are endorectal ultrasound (EUS) and magnetic resonance imaging (MRI). Furthermore, MRI can accurately predict the distance of the tumor to the colorectal membrane (CRM) and computed tomography (CT) is more suitable for detecting distant metastases. In the routine care of rectal cancer EUS is the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…With currently 3 Tesla MRI, sensitivity, specificity, and accuracy are expected to be substantially higher. Moreover, we cannot exclude that MRI accuracy rates in clinical routine may be substantially lower than in selective studies, as demonstrated for other modalities as well [23]. In the present analysis, all examinations were carried out by a variety of internal and external investigators reflecting routine daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…With currently 3 Tesla MRI, sensitivity, specificity, and accuracy are expected to be substantially higher. Moreover, we cannot exclude that MRI accuracy rates in clinical routine may be substantially lower than in selective studies, as demonstrated for other modalities as well [23]. In the present analysis, all examinations were carried out by a variety of internal and external investigators reflecting routine daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, pelvic MRI was a prerequisite for inclusion into the current analysis. During the study period, only 28% of all rectal cancer patients in the registry underwent pretherapeutic MRI [23], which greatly reduced the number of suitable subjects. Moreover, it was necessary to select a study period when the nationwide TME quality in routine care for rectal cancer had achieved an adequate level but neoadjuvant (chemo-) radiation, though recommended by the national guidelines [24], was not yet fully established.…”
Section: Discussionmentioning
confidence: 99%